THE GREEN VILLA MANAGEMENT MODEL FOR EFFICIENCY IN BALI LUXURY ACCOMMODATION - I Putu Mega Adi Adnyana; Gede Yoga Kharisma Pradana; Putu Devi Rosalina (CV. Lafadz Jaya, 2026)
Sustainable tourism has become a central paradigm in the global tourism industry, driven by increasing environmental pressures caused by accommodation activities. In Bali, particularly within the rapidly growing villa sector, challenges arise from high resource consumption and the lack of integration of environmentally friendly practices into operational management. This study aims to analyze the complexity and challenges of Green Villa implementation, evaluate its impact on operational efficiency, and develop an applicable management model at Javana Royal Villa. This research employs a qualitative approach using the Research and Development (R&D) method. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed descriptively through data reduction, display, and conclusion drawing. The findings indicate that Green Villa implementation involves moderate to high complexity with multidimensional challenges, including limited investment, absence of a dedicated person in charge, and varying staff understanding of sustainability practices. Despite these challenges, the implementation improves operational efficiency through better control of water and energy usage and a shift toward systematic monitoring. This study proposes a Managerial–Behavioral Based Green Villa Management Model integrating technical, managerial, and stakeholder aspects through the establishment of a Green Committee, integration of Green KPIs into SOPs, and strengthening of green organizational culture. Successful implementation depends on strong managerial commitment and the internalization of sustainable behavior.